Liquid-Crystal Nanomaterials Tribology and Applications - Ermakov, Sergey F. (Springer Series in Materials Science,, 2018)
This book discusses the tribological, rheological and optical properties of liquid-crystal nanomaterials as well as lubricant media. It also describes the formation of liquid-crystal materials and the application of cholesteric liquid-crystal compounds in technical friction units and in human and animal joints. Further, it shows the connection between the tribological and other physical properties of liquid-crystal cholesterol compounds and develops a lubricity conceptual model of cholesteric-nematic, liquid-crystalline nanostructures on the basis of physical and energetic interpretations. This general model is valid for all surfaces and friction pairs, including biopolymers, and could lead to applications of cholesteric liquid-crystalline nanomaterials in different friction units and tribosystems as well as in the treatment of joint diseases.